Post-caldera monogenetic volcanism at Deception Island, Antarctica: landform recognition and volcanic hazards implication - Pedrazzi, Dario; Kereszturi, G.; Lobo, Agustín; Geyer, Adelina; Calle, Janina (2020)
8th International MAAR CONFERENCE, Kamchatka, 24-30 August 2020 Interest in monogenetic volcanism, with special reference to volcanic hazards and risk studies, has risen in the last decade. This is especially true in areas where monogenetic volcanic fields are close to population centres, critical infrastructure, and shipping routes, as for example the Michoacán-Guanajuato and Chichinautzin Volcanic Fields in Mexico, Auckland Volcanic Field in New Zealand, Deception Island in the Antarctica, Garrotxa Volcanic Field and Canary Islands in Spain. Volcanic hazard assessment requires information to be obtained from the geomorphology of volcanic edifices and deposit characteristics, such as volumes, crater shapes, grain size distributions, and edifice geometries. Such attributes of a volcanic edifice often provide quantitative information for long-term eruptive volumes, magma eruption rates, and relative chronologies (Conway et al. 1998; Guilbaud et al. 2012). This research was supported by the MICINN grant CTM2011-13578-E and was partially funded by the POSVOLDEC project (CTM2016-79617-P) (AEI/FEDER-UE). A.G. is grateful for her Ramón y Cajal contract (RYC-2012-11024). D.P. is grateful for his Beatriu de Pinós (2016 BP 00086) and Juan de la Cierva (IJCI-2016-30482) contracts. This research is part of POLARCSIC and AntVolc activities.